Relationship between physical exercise and subjective wellbeing in university students: the chain mediation role of self-identity and self-esteem - Yao, Lihua; Guo, Kelei; Guo, Feng; Li, Dong; Liu, Yanying; Xiang, Jun (Frontiers in Psychology, 2025)
ObjectiveSubjective wellbeing, a fundamental concept in positive psychology, encompasses an individual’s evaluation of their life satisfaction and the balance between positive and negative emotions, thus reflecting personal perceptions and thoughts about life. This research aimed to analyze the interplay between physical exercise and subjective wellbeing among university students, with a particular emphasis on the mediating roles of self-identity and self-esteem. The study investigates the correlation between physical exercise and subjective wellbeing, further exploring how physical exercise affects self-identity and subsequently impacts subjective wellbeing. It also examines how self-identity influences self-esteem and the mediation role of self-esteem between self-identity and subjective wellbeing. This research constructed a chained mediation model encompassing physical exercise, self-identity, self-esteem, and subjective wellbeing to elucidate their interactions, ultimately proposing targeted exercise strategies to enhance subjective wellbeing through university physical education programs and personal exercise regimens.MethodsUtilizing physical exercise scales, self-identity scales, self-esteem scales, and subjective wellbeing questionnaires, this study conducted a survey among 913 university students. Data analysis proceeded via Pearson correlation analysis, structural equation modeling, and bias-corrected percentile bootstrap methods.ResultsPhysical exercise showed a positive correlation with subjective wellbeing (r = 0.49), exhibiting significant direct pathways from physical exercise to subjective wellbeing (β = 0.43, p < 0.01, CI [0.36, 0.50]). Physical exercise was also positively correlated with self-identity (β = 0.37, p < 0.01, CI [0.30, 0.44]) and self-esteem (β = 0.36, p < 0.01, CI [0.30, 0.43]), with self-identity positively influencing self-esteem (β = 0.31, p < 0.01, CI [0.23, 0.39]), both of which positively impact subjective wellbeing (self-identity: β = 0.17, p < 0.01, CI [0.11, 0.23]; self-esteem: β = 0.18, p < 0.01, CI [0.11, 0.25]). Furthermore, self-identity and self-esteem significantly mediated the relationship between physical exercise and subjective wellbeing through multiple pathways.ConclusionThese findings highlight a significant positive correlation between physical exercise and subjective wellbeing. Both self-identity and self-esteem serve as independent and sequential mediators in this relationship, underlining the complex interdependencies in the chain mediation model.